Dampak Dwelling Time Terhadap Layanan Ekspor Impor di Pelabuhan Tanjung Emas Semarang - Ario Hendartono; Christine Widilestari (Jurnal Maritim Polimarin, 2020)
Abstract The ideal dwelling time and in accordance with the target market profit must be seen as an interrelated system starting with the use of professional human resources, equipment readiness and time to prepare it, speed, maintenance, and not forgetting the kind and type, as well as the land, both the area affects the stacking of containers, distance and infrastructure that can support the acceleration of access needed to achieve high speed and efficiency. According to the World Bank (2011), dwelling time is the time calculated from the time the containers are unloaded and lifted from the ship until the containers leave the port container terminal through the main gate. The dwelling time process at the port consists of three stages, namely pre-clearance, customs clearance, and post-clearance. The objectives of this research include (1) To find out what factors cause the duration of dwelling time at TanjungEmas Port; (2) Knowing the impact of the duration of the dwelling time on export and import services at the Port of TanjungEmas; (3) Knowing the action of mitigation that taken by the Port of TanjungEmas Semarang to reduce dwelling time. The type of research used is qualitative research, which is a research process and understanding based on a methodology that investigates social phenomena and human problems with a case study model. It is expected that the data needed in research at TPKS can be obtained from the results of observations and interviews conducted related to matters of a policy, strategy and reality in the field. From the data obtained in the field, the following conclusions can be drawn: (1) The factors causing the length of dwelling time at TanjungEmas Port include: document and physical inspection process of goods on Customs classification;data on PIB and SPPB dates are often not detailed, the duration of time for container processing at TPKS is often unknown; service users do not clearly complete the document. (2) The impact of the dwelling time process on export and import services at TanjungEmas Port, among others: the export process does not really have an effect; The import process dwelling time is longer than the export process because the documents / containers that enter TPKS (Semarang Container Terminal ) must still be inspected by quarantine and Customs. (3) Mitigation action taken by the Port of TanjungEmas Semarang to reduce dwelling time include: detailed integration arrangements between TPKS and Customs through INSW facilities; 24 hours online facility equipped with modern equipment, namely ARTG (Automated Rubber Tired Gantry) and gate automation to expedite the process of releasing goods; the policy regulates the release of both filled and empty containers to the PLP after 5 days and after 10 days they must be moved again to a private depot.